An insight into market and non-market alternative food networks in Czechia during Covid-19 and beyond - Smutná, Zdeňka; Vávra, Jan; Duží, Barbora (Frontiers in Nutrition, 2024)
Introduction: The Covid-19 pandemic affected food systems in many countries and emphasized a lot of already existing social, economic and environmental agri-food problems. Alternative food networks (AFNs), praised for their ability to improve the food systems, were under stress, however, at the same time, the changed conditions may have opened new possibilities. In this paper we address the importance of AFNs during the pandemic and investigate how households have changed their participation in AFNs. Our research is novel by simultaneously focusing on both market and nonmarket AFNs which are often studied separately.Methods: A representative questionnaire study of Czech households was carried out in Autumn 2021 to provide a case study of food and consumption behaviour of the European country after several waves of Covid-19.Results and discussion: Based on the responses of 515 participants, the results show that 68% of Czech households participate in some form of AFN, be it shopping or food self-provisioning, i.e., non-market food procurement in the form of gardening. Focusing on the market AFNs, farmers' markets and farm gate sales are the most popular. Covid-19 and 2021 emerging economic pressures led to a decrease of consumption of organic food (22% of respondents) as well as fresh fruit and vegetables in general (10% of respondents) and a noticeable occurrence of food insecurity (18% of households). Based on these findings, the paper discusses the ability of AFNs to support food and nutritional resilience. Problems which may endanger market-oriented AFNs are discussed as well.Conclusion: By addressing both market and non-market AFNs, the paper brings new knowledge into the food environment and agri-food policies research.